Kinning as intimate disaster response: from recuperation in host families to educational migration of the Chernobyl children from Belarus to Italy. Issue 2 (4th March 2022) - Zhukova, Ekatherina
ABSTRACT: This article brings the concept of kinning from anthropology and the sociology of adoption and care work to the study of disaster response and migration. It looks at intimate relationships between the Chernobyl children from Belarus and host families in Italy within the humanitarian programme of child recuperation abroad and argues that these relationships can be understood as kinning. Kinning implies intimate disaster response, a process of fostering transnational relations at a people-to-people level during humanitarian assistance independently of non-state, state, and supranational institutions. The manuscript shows that kinning with host families in childhood resulted in educational migration of the grown-up Chernobyl children to Italy in adulthood. The essay concludes that disaster response and migration studies can benefit from studying the private and the personal in order to understand the mobility trajectories of disaster survivors. This is important when disaster survivors are children and disaster response and migration overlap with coming of age.